Filosofi Nuwun Sewu sebagai Pedoman Kehidupan dalam Mencegah Tindak Kekerasan - Sukron Mazid; Achmad Busrotun Nufus; Danang Prasetyo (Ideas Publishing, 2022)
The purpose of this study is to explore the role of civilizing nuwun sewu in people's lives, especially the younger generation whose urgency is as an effort to prevent and handle cases of violence in the community. This type of research is descriptive qualitative based on the philosophy of postpositivism, the researcher is the key instrument. Data collection techniques were conducted by interview, documentation, focus group discussion, and observation. The research subjects were determined using a purposive method that was adapted to the research objectives, namely community leaders, humanists, and academics. The results of this study indicate that the culture of nuwun sewu can be carried out in the community, education, social activities, and work need to be practiced so that the nuwun sewu culture becomes a tradition and habit and of course it can be recommended as a formula to prevent acts of violence, this effort is a procedure for attitudes and behavior. small examples of behavior that will have a big impact in daily life, especially to prevent acts of violence. The culture of nuwun sewu needs to be used as a guide and guide, especially the Javanese people in respecting and respecting others.